Penyelesaikan Soal Geometri Ruang Ditinjau dari Tingkat Kecerdasan Visual Spasial Siswa Kelas XII IPA SMA Negeri 2 Mejayan : Analisis Kemampuan Reprentasi Matematis Siswa - Hendradi, Franc (JPT : Jurnal Pendidikan Tematik, 2021)
This study aims to: 1) describe students' mathematical representation abilities in solving geometry problems in terms of spatial visual intelligence; 2) Knowing the factors that affect students' mathematical representation ability in solving geometry problems. This research is a descriptive qualitative research. The subjects in this study consisted of 9 students of class XII science at SMA Negeri 2 Mejayan who were categorized into high, medium and low categories based on a visual-spatial intelligence test. The sample selection technique in this study was purposive sampling. Data collection in this study was done by tests and interviews. The triangulation used in this research is method triangulation and source triangulation. Data analysis carried out includes data reduction, data presentation, and drawing conclusions. The results of this study concluded that students with high spatial intelligence have good mathematical representation skills. Students with high spatial intelligence are able to present problems using pictures, involve pictures to solve problems, understand mathematical symbols, make mathematical symbols, use mathematical models to solve problems, make problem situations in verbal form and make conclusions from answers. Students with moderate spatial intelligence have good mathematical representation skills. Students with moderate spatial intelligence are able to present problems using pictures, but in involving pictures to solve problems they are still not precise, understand mathematical symbols, make mathematical symbols, use mathematical models to solve problems, make problem situations in verbal form and make conclusions from answer. Students with low spatial intelligence have poor mathematical representation skills. Students with low spatial intelligence have not been able to construct images well, the symbols written are also still not sufficient to represent the problem and are unable to explain how to solve the problem. Factors that affect the ability of mathematical representation are related to the learning process, the media used, learning resources, the variety of questions used by teachers and factors from students.